2018
DOI: 10.1038/s41570-018-0001-2
|View full text |Cite
|
Sign up to set email alerts
|

Earth-abundant transition metal catalysts for alkene hydrosilylation and hydroboration

Abstract: The addition of a silicon-hydrogen or a boron-hydrogen bond across a carbon-carbon multiple bonds is a well-established method for the introduction of versatile silane and borane functional groups to base hydrocarbon feedstocks. Transition metal catalysis, historically with precious second- and third- row transition metals, has been used to broaden the scope of the hydrofunctionalization reaction, improve reaction rate and enhance selectivity. The anti-Markovnikov selectivity of platinum-catalyzed hydrosilylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
404
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 711 publications
(408 citation statements)
references
References 147 publications
3
404
0
1
Order By: Relevance
“…3). Considering the widespread hydroxyl and amino groups in biomolecules, propargyl derivatives from them were selected as representatives in most cases (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Propargyl ether analogues of menthol, carveol, prolinol, glucose and glucofuranose were successfully transformed into corresponding α-vinylsilanes in good to excellent yields (30-34).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Considering the widespread hydroxyl and amino groups in biomolecules, propargyl derivatives from them were selected as representatives in most cases (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Propargyl ether analogues of menthol, carveol, prolinol, glucose and glucofuranose were successfully transformed into corresponding α-vinylsilanes in good to excellent yields (30-34).…”
Section: Resultsmentioning
confidence: 99%
“…1 H and 13 C NMR Spectra of all hydrosilylation products and unknown substrate were provided. 13 C DEPT135 NMR Spectra of products 3,4,5,6,7,9,10,12,13,15,19,20,21,26,30,31,32,36,37,38,39,40,41,42,44,45 were afford. 2D NOESY Results of products 1 and 27 are also provided.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent research in this area has focused on the development of earth abundant transition metal catalysts of Fe, Co and Ni. [58] Due to their Lewis acidity, few s- [59] and p-block [60][61][62][63][64][65] compounds have been explored as possible alternatives to the existing catalysts.…”
Section: Bond Lengths [å]mentioning
confidence: 99%
“…This is born out experimentally:d espite the apparent CÀCs ingle bond present in the cyclic core of 7,d issolution of pure crystals of this compound in C 6 D 6 led to the generation of small amounts of both 1 and C 2 H 4 .T hus, to our surprise, the cycloaddition of ethylene to 1 is in fact reversible. [24] Circumstantial evidencef or the intermediate generation of 8 came from the isolationo f one or two crystalso ft his compound by the low-temperature reactiono f1 with excess ethylene, followed by storagea t À30 8Cfor two weeks. Although a computational investigation for the reaction of 1 with ethylene suggested that 7 may readily undergo af urtherc ycloaddition event with ethylene to form the six-membered metallasilacycle 8 (Scheme 3, Figure 3), we were surprised to find that the experimentally observed product from the reaction of 1 with excess ethylene is the alkene-Ni 0 p-complex 9.…”
mentioning
confidence: 99%